Software protection technology based on code fragmentation - Jingcheng GUO; Hui SHU; Xiaobing XIONG; Fei KANG (网络与信息安全学报)
Aiming at the shortcomings of the current software protection technology,a code fragmentation technology was proposed.This technology is a new software protection technology that takes functions as units,shells functions,randomizes memory layout,and performs dynamic linking.The code shellization realizes the position-independent morphing of code fragments,the memory layout randomizes the random memory loading of the code fragments,the dynamic linking realizes the dynamic execution of the code fragments,and the program fragmentation processing is achieved through the above three links.The experiments show that the code fragmentation technology can not only realize the randomization of the memory location of function fragments during program execution,but also the dynamic link execution of function fragments,increasing the difficulty of static reverse analysis and dynamic reverse debugging of the program,and improving the anti-reverse analysis ability of the program.